Cracks path growth in turbine blades with TBC under thermo – mechanical cyclic loadings (Fracture and Structural Integrity, 2015)
Blades of combustion turbines are extremely loaded turbojet elements, which transmit operative energy onto a rotor. Experiences of many years indicate, that cracks initiation and propagation in the blades during the operation time can cause destruction not only of the engine, but sometimes an airplane. In high temperature one of the most often occuring interactions in the turbine engine are time variable force fields, caused by non-stationary flowing of an exhaust gas and aerodynamical interaction of the engine elements. The extremal thermo-mechanical loadings initiate gradual degradation process of the blades as a result of fatigue and material creep. More often Thermal Barrier Coatings (TBCs) are applied on the turbine blade surface to provide protection not only against the high temperature but also against aggressive environment. The paper presents the advantages of applying of the TBC layers for increase of the cracks resistance to gradual degradation of the turbine blades. The level of save values of thermo-mechanical loading was estimated. Analysis of critical values of loading leading to crack initiation, further growth and the final blade fragmentation was performed. The most efforted places of the turbine blades were selected and crack paths due to thermo-mechanical cyclic loading were determined.
Keywords: Turbine blade; Thermal barrier coating; Finite element method